2017
DOI: 10.1007/s10661-017-6327-2
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter levels in a South American megacity: the metropolitan area of Lima-Callao, Peru

Abstract: The temporal and spatial trends in the variability of PM and PM from 2010 to 2015 in the metropolitan area of Lima-Callao, Peru, are studied and interpreted in this work. The mean annual concentrations of PM and PM have ranges (averages) of 133-45 μg m (84 μg m) and 35-16 μg m (26 μg m) for the monitoring sites under study. In general, the highest annual concentrations are observed in the eastern part of the city, which is a result of the pattern of persistent local winds entering from the coast in a south-sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 22 publications
1
59
0
21
Order By: Relevance
“…In the city of Lima, PM 2.5 concentrations vary by seasonality based on meteorological conditions. In late autumn and winter (lower temperatures), the gas-particle conversion processes increase the environmental PM 2.5 concentrations [13]. Another possibility is that the virus could be loaded onto the particulate matter (PM), which then acts as a vector for infection spread, extending the persistence of the viral particles in the air, thereby favoring an "indirect" transmission in addition to the direct spread (individual to individual) [5].…”
Section: Several Studies Have Explored the Association Between Sars-cmentioning
confidence: 99%
“…In the city of Lima, PM 2.5 concentrations vary by seasonality based on meteorological conditions. In late autumn and winter (lower temperatures), the gas-particle conversion processes increase the environmental PM 2.5 concentrations [13]. Another possibility is that the virus could be loaded onto the particulate matter (PM), which then acts as a vector for infection spread, extending the persistence of the viral particles in the air, thereby favoring an "indirect" transmission in addition to the direct spread (individual to individual) [5].…”
Section: Several Studies Have Explored the Association Between Sars-cmentioning
confidence: 99%
“…In Peru, studies of the chemical composition and water-soluble ions from particulate matter are scarce in the scientific literature. For instance, Silva et al [25] studied PM 10 and PM 2.5 concentrations levels measured from 2010 to 2015 in the Metropolitan area of Lima-Callao. The results showed that PM 2.5 concentrations exceeded the Annual World Health Organization (WHO) thresholds and the national air quality standards (ECA).…”
Section: Introductionmentioning
confidence: 99%
“…We described bacterial community shifts along an altitude gradient from the Upper Rimac zone (1 500 -4 500 msl) to the Middle (300 -1 500 msl) and Lower Rimac zones (0 -300 msl). The Lower Rimac crosses the Lima Metropolitan area, a megacity situated on the hyper-arid Peruvian desert [4,32], being an essential water source for this city.…”
Section: Discussionmentioning
confidence: 99%
“…Lima, the capital city of Peru, is the second largest desert city in the world [3]. Its Metropolitan area is inhabited by more than 10 million people creating enormous challenges for environmental and public health [4]. For instance, it has been shown that water quality in Lima is a significant risk factor for pathogenic infections in children [5].…”
Section: Introductionmentioning
confidence: 99%